Application of hydrant piping system design in boiler plants for fire safety systems in paper producing companies - Achmad Imam Suyuthi; Sufiyanto Sufiyanto; Boe Tong Widada (Jurnal Penelitian, 2022)
As one of the important components, hydrants must be present in the boiler plant, whose function is to extinguish the fire in the event of a fire incident in the area. The working principle of the hydrant system is that when an event of fire occurs, the suction pump will take water from the ground reservoir, later on the water will flow into the pipe leading to the pillar hydrant, and the fire hose will be disconnected from the pillar hydrant to extinguish the burning area. The issue needs to be solved in this research is to design a hydrant piping system in the boiler area of PT Mekabox Internasional that meets the standards used by the industries. The purpose of designing this hydrant piping system is to find out how much flow is in the hydrant if the boiler plant area has an area of 2016 m2, how thick the pipe should be, and how many pillar hydrants are necessary. The scope of the research discussion includes hydrant piping systems, hydrant piping calculations, and standards used in hydrant piping systems. The results of the calculation and data processing of this hydrant system design are; the number of pillar hydrants needed in an area of 2016 m2 is 2 pillar hydrants, the required water discharge is 432 m3 with the assumption that the blackout time is 2 hours, and the pipe diameter required is 6 inches and must have a pipe thickness of 6 mm. The results of the hydrant piping system design on the boiler plant can be applied directly to the company.